2019
DOI: 10.1109/tbme.2018.2836317
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Higher Frequency Microwave Ablation in the Presence of Perfusion

Abstract: Higher-frequency microwave ablation is appealing because it allows for more flexibility in antenna design. A critical issue concerning the feasibility of higher-frequency microwave ablation, considering its strong dependence on heat diffusion to grow thermal lesions, is its performance in strongly perfused environments. This work shows that higher-frequency microwave ablation achieves thermal lesions comparable to those from microwave ablation performed at conventional frequencies in both non- and strongly per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…The objective of ablation procedures is to heat the targeted tissue, consisting of the tumor and a margin of surrounding tissue, to cytotoxic temperatures. While most systems in current clinical use operate at 915 MHz or 2.45 GHz, systems operating at other frequencies in the microwave range have been proposed …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of ablation procedures is to heat the targeted tissue, consisting of the tumor and a margin of surrounding tissue, to cytotoxic temperatures. While most systems in current clinical use operate at 915 MHz or 2.45 GHz, systems operating at other frequencies in the microwave range have been proposed …”
Section: Introductionmentioning
confidence: 99%
“…While most systems in current clinical use operate at 915 MHz or 2.45 GHz, systems operating at other frequencies in the microwave range have been proposed. 2,3 Computational models are widely used to guide the design and optimization of MWA applicators, to comparatively assess the impact of energy-delivery strategies on ablation outcome, and for characterizing applicator performance in a variety of tissue types. 1,[4][5][6][7][8] Computational models are also being developed for use as treatment planning tools that may assist a physician in selecting treatment parameters that maximize the likelihood of achieving a favorable treatment outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the MWA studies reported in the previous literature have been conducted utilizing the electromagnetic wave frequency of 915 MHz or 2.45 GHz, with a few studies also reported at higher frequencies (see e.g. (Sawicki et al, 2017, Luyen et al, 2014, Sawicki et al, 2018, Yoon et al, 2011). The electric and magnetic fields related to the time-varying transverse electromagnetic wave can be computed from the Helmholtz harmonic wave equation derived from Maxwell's equation and is given by:…”
Section: Modelling Of Heat Source For Mwa and Rfamentioning
confidence: 99%
“…A variety of tissue-mimicking phantoms with tunable dielectric properties have been reported in the literature. 43,44 Measurement of the antenna’s specific absorption rate (SAR) pattern may be helpful for assessing the radiation pattern of an antenna, but neglects the effects of thermal conduction on ablation zone profiles. 45 Furthermore, SAR measurements typically do not account for the changes in antenna radiation pattern due to temperature-dependent changes in tissue dielectric properties.…”
Section: Mw Ablation Applicatorsmentioning
confidence: 99%
“…46 To account for effects of blood perfusion, which acts as a heat sink, ablation zones must be evaluated in an in vivo animal model or by emulating the perfusion using a perfusion chamber. 47,48 Ablated tissue is resected after in vivo ablations for histopathologic analysis; viability stains may assist in accurate determination of the ablation zone boundary.…”
Section: Mw Ablation Applicatorsmentioning
confidence: 99%